Canadian Taxpayers Investing in U.S. Real Estate - Lareau, André (Revue générale de droit, 1986)
A fair amount of Canadian taxpayers spend a substantial period of the year in the United States while retaining their Canadian resident status. New income tax rules in the United States related to the notion of residence play an important rule in the planning of the life of a taxpayer. The first part of this paper focuses on the American legislation in order to warn the taxpayers about the potential income tax consequences of spending time in the United States.The second part of this paper analyses the U.S. income tax legislation related to Canadian taxpayers who invest in U.S. real estate. Should the taxpayer use a corporation to hold the investment? Should that corporation be Canadian or American? These questions trigger a number of potential tax problems, some of which are discussed in this paper.